2022
DOI: 10.3389/fmolb.2022.956500
|View full text |Cite
|
Sign up to set email alerts
|

Regulation and physiological functions of phoenixin

Abstract: Phoenixin is a newly discovered neuropeptide generated from small integral membrane protein 20. Phoenixin is a ligand for the G protein-coupled receptor 173 (GPR173) and has been detected in central and peripheral tissues of human, rats, mice, bovine, and zebrafish. It was initially involved in regulating reproductive function by stimulating the luteinizing hormone release from pituitary cells by increasing the level of gonadotropin-releasing hormone. Recently, many functions of phoenixin have been generalized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 79 publications
0
14
0
Order By: Relevance
“…Expression of PNX and its receptor GPR173 in the arcuate nucleus and paraventricular nucleus, which are closely related to the regulation of food intake in the brain, led scientists to speculate that PNX may have a potential role in regulating food intake 9 . Subsequently, animal model studies began to be reported on the effect of PNX on food intake.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Expression of PNX and its receptor GPR173 in the arcuate nucleus and paraventricular nucleus, which are closely related to the regulation of food intake in the brain, led scientists to speculate that PNX may have a potential role in regulating food intake 9 . Subsequently, animal model studies began to be reported on the effect of PNX on food intake.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are many PNX isoforms with different amino acid lengths, all formed by cleavage from the same precursor peptide; PNX-14 and PNX-20 are the most predominantly expressed isoforms [7,11] Therefore, most of the studies related to PNX in the literature have been done on PNX-14 and PNX-20 isoforms. Expression of PNX and its receptor GPR173 in the arcuate nucleus and paraventricular nucleus, which are closely related to the regulation of food intake in the brain, led scientists to speculate that PNX may have a potential role in regulating food intake [9]. Subsequently, animal model studies began to be reported on the effect of PNX on food intake.…”
Section: Median (Iqr) Mean ± Sd Median (Iqr) Mean ± Sd P-valuementioning
confidence: 99%
See 1 more Smart Citation
“…By inducing the expression of gonadotropin-releasing hormone receptor and increasing gonadotropin-releasing hormone, PNX stimulates luteinizing hormone (LH) release in pituitary cells of female mice [ 9 ]. Two active forms of PNX were discovered in mice, including PNX-14 and PHN-20 [ 10 ]. Chi [ 11 ] claimed that PHN-20 alleviated the pathological symptoms of gestational diabetes mellitus by repressing OS and inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Phoenixin (PNX) was first isolated from rat hypothalamus and bovine heart and has been identified in numerous mammals and non-mammals, which is expressed in various central and peripheral tissues and induces the activation of G-protein-coupled receptor (GPR173) [ 16 ]. PNX was speculated to play a role in multiple levels of the hypothalamus-pituitary-gonad (HPG) axis [ 17 ].…”
Section: Introductionmentioning
confidence: 99%